Expert stakeholder perspectives on preventative training and testing in snowsport: exploring current practices, challenges, and opportunities - Balsiger, P.; Monsonís, O. B.; Scherr, J.; Verhagen, E.; Bolling, C.; Spörri, J. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Competitive snowsports such as alpine skiing, freestyle skiing and snowboarding are known to be high-risk sports. 1 Preventative training and testing may be considered promising countermeasures. 2 The aim of this study was to explore current practices, challenges and opportunities related to preventative training and testing in snowsports.